Dietary Supplementation with Methylsulfonylmethane and Myo-Inosito Supports Hair Quality and Fecal Microbiome in Poodles - Jie Zhang; Dan Guo; Limeng Zhang; Deping Li; Baichuan Deng (Animals)
This study aimed to investigate the effects of dietary supplementation with methylsulfonylmethane (MSM) and myo-inositol (MI) on hair quality, fecal microbiota, and metabolome in poodles. Thirty-two adult poodles categorized based on initial body weight and sex were randomly assigned to four groups. These groups (designated the CON, MSM, MI, and MSM + MI groups) received a basal diet, the same diet supplemented with 0.2% MSM + 0% MI, the same diet supplemented with 0% MSM + 0.2% MI, or the same diet supplemented with 0.2% MSM + 0.2% MI, respectively. The study lasted for 65 days. During the entire study period, body weight, average daily weight gain, feed intake, energy intake, and fecal output were normal in all the animals and did not differ significantly among the treatment groups. Hair scale thickness was lower in the MI and MSM + MI groups than in the CON group on Day 65 (p < 0.05). An amino acid analysis of the hair revealed higher sulfur content in the MI and MSM + MI groups on Day 65 than on Day 0 (p < 0.05). Moreover, the poodles in the MSM, MI, and MSM + MI groups presented significantly lower levels of Proteobacteria_unclassified and Candidatus Phytoplasma than did those in the CON group. The relative abundance of Gammaproteobacteria_unclassified was greater in the MSM and MI groups than in the CON group (p < 0.05). The MSM group presented a greater abundance of Glucerabacter than the CON group (p < 0.05). Compared with those in the CON and MSM + MI groups, the abundances of Paramuribaculum and Hafnia in the MSM group were greater (p < 0.05). The abundances of Enterobacter and Kineothrix were greater (p < 0.05) in the MI group than in the CON and MSM + MI groups. The poodles in the MI group presented significantly greater abundances of Bacteroidales_unclassified, Halanaerobium, Mycobacterium, and Erysipelotrichaceae_unclassified than did poodles in the CON, MSM, and MSM + MI groups. Fecal metabolomics analysis revealed that MSM, MI, and MSM + MI treatment markedly affected carbohydrate metabolism. MSM + MI treatment also influenced lipid metabolism. These findings suggest that dietary supplementation with MSM and MI can improve the hair quality of poodles.